2006
DOI: 10.1136/jnnp.2006.097808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and predictive factors of intraventricular rupture in patients who have bacterial brain abscesses

Abstract: Background: Intraventricular rupture of brain abscesses (IVRBA) remains a catastrophic and fatal complication of bacterial brain abscess (BBA). However, no information has been reported about the risk factors that are predictive of intraventricular rupture. Methods: This study was undertaken to determine the potential risk factors that are predictive of intraventricular ruptures in patients with BBA but without intraventricular rupture when arriving at the hospital. A comparison is also made between patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 23 publications
(29 reference statements)
1
47
0
1
Order By: Relevance
“…6) Surgical treatment can involve either aspiration or excision of the abscess. The choice of procedure has been the subject of much debate.…”
Section: Discussionmentioning
confidence: 99%
“…6) Surgical treatment can involve either aspiration or excision of the abscess. The choice of procedure has been the subject of much debate.…”
Section: Discussionmentioning
confidence: 99%
“…complication of brain abscesses; factors associated with increased risk of rupture include deep location, location close to a ventricle wall, and the presence of multiple abscesses. 23 …”
Section: Surgical Treatmentmentioning
confidence: 99%
“…30 The most typically isolated microorganisms are Streptococcus and Staphylococcus species. 6,16,19,23,34,40,44 In a review of 130 cases, Tseng and Tseng 40 reported that multiple organisms were identified in 23% of patients. Goodkin et al 12 reported that Ͼ 1 organism was isolated in 39% of 36 positive cultures.…”
Section: Laboratory Studiesmentioning
confidence: 99%
See 2 more Smart Citations